Development and Application of Loop-Mediated Isothermal Amplification Assays for Rapid Visual Detection of cry2Ab and cry3A Genes in Genetically-Modified Crops - Li, Feiwu (MDPI, 2014)
The cry2Ab and cry3A genes are two of the most important insect-resistant exogenous genes and had been widely used in genetically-modified crops. To develop more effective alternatives for the quick identification of genetically-modified organisms (GMOs) containing these genes, a rapid and visual loop-mediated isothermal amplification (LAMP) method to detect the cry2Ab and cry3A genes is described in this study. The LAMP assay can be finished within 60 min at an isothermal condition of 63 °C. The derived LAMP products can be obtained by a real-time turbidimeter via monitoring the white turbidity or directly observed by the naked eye through adding SYBR Green I dye. The specificity of the LAMP assay was determined by analyzing thirteen insect-resistant genetically-modified (GM) crop events with different Bt genes. Furthermore, the sensitivity of the LAMP assay was evaluated by diluting the template genomic DNA. Results showed that the limit of detection of the established LAMP assays was approximately five copies of haploid genomic DNA, about five-fold greater than that of conventional PCR assays. All of the results indicated that this established rapid and visual LAMP assay was quick, accurate and cost effective, with high specificity and sensitivity. In addition, this method does not need specific expensive instruments or facilities, which can provide a simpler and quicker approach to detecting the cry2Ab and cry3A genes in GM crops, especially for on-site, large-scale test purposes in the field.